THU0541 Amyloidosis in Alkaptonuria in a Cohort of Italian Patients. (9th June 2015) - Millucci, L.; Braconi, D.; Marzocchi, B.; Galeazzi, M.; Frediani, B.; Bardelli, M.; Bernardini, G.; Geminiani, M.; Gambassi, S.; Orlandini, M.; Sestini, S.; Santucci, A.
Abstract : Background: Alkaptonuria (AKU) is an ultra-rare disease developed from the lack of homogentisic acid oxidase activity, causing homogentisic acid (HGA) accumulation that produces an ochronotic pigment of unknown composition. The role of proteins has been hypothesized as additional causal factors of ochronosis. Evidence has been provided on the presence of serum amyloid A (SAA) in AKU tissues (1-5), which allows classifying AKU as a secondary amyloidosis (6). Objectives: To collect direct and indirect indications of secondary amyloidosis in AKU patients and find a correlation between serum levels of inflammation and oxidative stress markers and clinical parameters. Methods: In a cohort of 15 Italian AKU ochronotic patients an analysis for amyloid in different tissues has been carried out, adopting Congo Red, Thioflavin T and SAA-immunofluorescence staining. Tissues were also probed for the presence of inflammation and lipid peroxidation. Clinical parameters as osteopenia of the hip, kyphosis, scoliosis, fractures, disc disease of the thoracic and lumbar spine and joint disease as assessed by MRI or X-ray, range of joint and spine motion were assessed. Patient sera were analysed for inflammation (SAA, CRP) and oxidative stress (AOPP, TAC) markers. Results: Amyloid, ochronosis, lipid peroxidation, inflammation, tissue calcification, cell death and tissue degeneration were found to co-localize in AKU. These findings are in very good agreement with high plasma SAA levels and other clinical and biochemical diagnostic parameters in AKU patients and related to HGA-induced oxidative stress. Conclusions: AKU is a complicating inflammatory multisystemic disease, where any body district expressing HGD may be affected by ochronosis and related AA amyloidosis. A chronic inflammatory status experienced by patients, paralleled by inadequate antioxidant defences, may thus promote the synthesis of amyloidogenic proteins ultimately leading to secondary amyloid deposition, which is in turn cytotoxic, pro-inflammatory and pro-oxidant, further complicating AKU pathogenic lesions and clinical deterioration of AKU patients. References: L. Millucci, et al. Secondary amyloidosis in an alkaptonuric aortic valve. Int J Cardiol. 2014 1; 172: e121–e123. A. Spreafico et al. Antioxidants inhibit SAA formation and pro-inflammatory cytokine release in a human cell model of alkaptonuria. Rheumatology (Oxford) 2013 52: 1667–1673. L. Millucci et al. Diagnosis of secondary amyloidosis in alkaptonuria. Diagn Pathol. 2014; 9: 185 L. Millucci, et al. Amyloidosis, Inflammation, and Oxidative Stress in the Heart of an Alkaptonuric Patient. Mediators Inflamm. 2014; 258471. L. Millucci et al. Chondroptosis in alkaptonuric cartilage. J Cell Physiol. 2015 23:1148-57. L. Millucci et al. Alkaptonuria is a novel human secondary amyloidogenic disease. Biochim Biophys Acta 2012 1822: 1682–1691. Disclosure of Interest: None declared